Strategic Agility in SMES: How Digital Transformation Shapes Competitive Avantage in Emerging Market - Jemmy, Jemmy (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
In the context of emerging markets marked by volatility, uncertainty, and technological disruption, digital transformation has become a crucial enabler of strategic agility for Small and Medium Enterprises (SMEs). This study explores how digital capabilities contribute to strategic agility and, subsequently, to the competitive advantage of SMEs. A mixed-methods approach was employed, combining quantitative data from 300 SMEs across Indonesia, Vietnam, and Ghana with qualitative case studies from five selected firms. Quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) confirmed that digital capabilities significantly enhance both strategic agility and competitive advantage. Moreover, innovation culture and external collaboration were found to be significant moderating variables in these relationships. Qualitative findings support these results, revealing that digital maturity reflected in process reorientation, platform integration, and data-driven responsiveness enables SMEs to adapt and innovate under uncertainty. The findings provide actionable insights for policymakers and practitioners seeking to enhance SME resilience through inclusive digital strategies. This study contributes to the extension of dynamic capabilities theory by integrating cross market agility responses into the framework of digital transformation in emerging economies.